FPGA Implementation of Hardware Efficient Algorithm for Image Contrast Enhancement Using Xilinx System Generator. (2016) - Wilson, Garnet; Premson, Y.
Abstract: Contrast enhancement plays an important role in generating high quality images for image processing applications, such as digital image or video photography, liquid crystal display processing, and medical image analysis. For achieving real-time performance for high-definition video applications, it is necessary to design efficient contrast enhancement hardware architecture to meet the needs of real-time processing. In this paper, a Modified Adaptive Gamma Correction with Weighting Distribution algorithm is explained for contrast enhancement. This novel hardware-oriented contrast enhancement algorithm is modeled in Xilinx System Generator and implemented in FPGA using Zed Board XC7Z020. This hardware-oriented contrast enhancement algorithm achieves good image quality by measuring the results of qualitative and quantitative analyzes. This Modified Adaptive Gamma Correction with Weighting Distribution algorithm exhibits better contrast and high PSNR value than that of the existing Adaptive Gamma Correction with Weighting Distribution algorithm.